Group‐urotherapy for children with complex elimination disorder: An Australian study. Issue 3 (6th May 2022) - Peck, Blake; Terry, Daniel; Martin, Benita; Matthews, Belinda; Green, Andrea
Abstract: Elimination disorders are common in children and are associated with increased levels of psychological distress for both the child and their family. Despite successful treatments for elimination disorders, 30% of children do not respond to standard treatments to achieve continence. In these cases, a Urinary and Faecal Incontinence Training Program for Children and Adolescents (UFITPCA) has been established as an adjunct to existing therapy. The aim of the study is to explore the experiences of children who participated in the program. A qualitative design was employed with female children, aged 7–8 years, ( n = 4) who participated in the UFITPCA program participated in a 60‐min focus group interview. The parents of the children ( n = 4) were also interviewed. Data was collected at the end of the 9‐week program and analysed to identify themes that encompassed the experiences of the UFITPCA program and associated outcomes amongst both the children and their parents. Three central themes were emerged from the data, which included: Make it Stop, I'm not Alone, and Look at what I can do now. These findings were encapsulated by the desperation and frustration of children and parents prior to commencing the program; the widespread positive implications for the children's wellbeing from having engaged in a program with others just like them, and their sense of satisfaction of putting their newfound knowledge into practice. Both children and parents recognized a change in their child's overall sense of wellbeing and parents identified that their children felt more in control of symptoms and how they responded when symptoms arose. The children experienced an increase in their acceptance and self‐efficacy of their symptoms.